Scalable nanoconfined GO/SWCNT-OH membranes for efficient high-salinity organic wastewater treatment - Yechen An; Xiaoxu Gao; Jing-Long Han; Yuting Ning; Xinping Fu; Ruiyun Ren; Liang Mei; Wenli Jiang; Ruifeng Yan; Jun Cui; Yu Tao; Aijie Wang (Water Research, 2026)

An EGFR-directed photoimmunotheranostic conjugate enables tumor-specific imaging and potent synergistic antitumor activity - Tongshu Wu; Xinyu Cui; Yuting Tian; ZiHui Wang; Weijie Han; Dianlong Jia; Jun Li; Jinjie Chang (Journal of Photochemistry and Photobiology B: Biology, 2026)

Overlooked role of submerged macrophytes in the seasonal persistence of odor-producing Pseudanabaena - Zhijie Cui; Changtao Yang; Limin Ma; Xiaoyan Gu; Xiaobing Shen; Bin Wan; Yuwei Tao; Yuting Sang; Yong Liu; Qinghui Huang (Journal of Environmental Sciences, 2026)

Neural identification of self-emitted vocalizations in the auditory midbrain of behaving bats - Huan Ye; Zhongdan Cui; Zhenxu Liu; Xuejiao Qin; Xincao Huang; Yuting Bai; Jinhong Luo (Science China Life Sciences, 2026)

Qualification rates and post-treatment spring regrowth reveal divergent efficacy of ten Spartina alterniflora control methods: evidence from 848 field-managed patches - Wanxia Yang; Yichen Cui; Yuting Cen; Yi Liu; Xiaoqiang Lu (Journal of Environmental Management, 2026)

Water–sediment multi-objective synergetic scheduling of reservoirs considering reservoir–river coupling: a case study of the Middle and Lower Yellow River - Wei Zhang; Hefei Huang; Chengguo Su; Peilin Wang; Yanan Kong; Yuting Cui (Environmental Modelling & Software, 2026)

Modulating Ti-O-Bi-based charge transport channels across Bi6O7/Ti3C2Tx interface for augmented targeted iodide ion removal via capacitive deionization - Nan Feng; Xinping Fu; Mingxing Liang; Yuting Ning; Chenghao Li; Tongtao Fan; Huan Zhang; Wei Yao; Donghai Yuan; Jun Cui (Chemical Engineering Journal, 2026)

Artemisinin derivative SM934 targets α-enolase to inhibit PEP-mediated TAK1 stabilization and inflammation - Jun Pan; Yuwei Zhang; Zhiwei Du; Yuanyuan Huang; Yu Wang; Miya Su; Yuting Cai; Weiya Xu; Lili Chen; Chengdong Huang; Di Cui; Dongsheng Chen; et al. (Science China Life Sciences, 2026)

Organophosphate triesters and diesters in the Yellow River Basin (Shandong section): Geographical patterns, land use correlates and compound-specific source apportionment - Yuting Ren; Lin Zhu; Huijie Dang; Lili Cui; Ang Zhao; Chao Wei; Mei Wang (Marine Pollution Bulletin, 2026)

Phase-modulated engineering of oxygen-doped molybdenum disulfide for boosting visible light-driven photocatalytic tetracycline degradation - Ze Yuan; Chenghao Li; Nan Feng; Xinping Fu; Yuting Ning; Wei Yao; Lepu Ci; Jun Cui (Journal of Environmental Chemical Engineering, 2026)

Phosphorylation-modified fava bean 11S protein fibril-based oleogels: A novel strategy to enhance network flexibility and alter rheological and textural properties - Zhihao Xu; Xuemei Lin; Wenzhong Zhao; Xiaoqi Ding; Xianglin Sun; Yuting Ding; Hui Chen; Pengbo Cui (Food Hydrocolloids, 2026)

Ubiquitous and remarkable tire-derived chemicals (TDCs) contamination in road-related environmental receptors across the Tibetan plateau - Qianyuan Yang; Wei Zhou; Qiangying Zhang; Wenxiao Pan; Xiaomei Cui; Yuting Dong; Jifu Liu; Chuanlong Zhang; Duo Bu; Aiqian Zhang; Jianjie Fu; Guibin Jiang (Environmental Research, 2026)

Oligomer production and effects on gut microbiota of PLA and PBAT biodegradable microplastics in in vitro digestion model - Guowei Ma; Xiaomeng Gao; Zhihui Li; Yuting Chen; Hanfei Li; Yiling Cui; Peixue Guo; Biao Yang; Di Feng; Tingting Zhao (Food Bioscience, 2026)

Shifting Biological Drivers Govern Drought and Wetting Legacies on Soil Respiration - Yanan Cui; Stefano Manzoni; Zhiyuan Quan; Daiqi Zhao; Lina Yan; Chengliang Wang; Jidong Liao; Jiancheng Yu; Yuting Liu; Yanan Li; Wei Sun; Baoku Shi (Global Change Biology, 2026)
Climate change is intensifying precipitation extremes, yet how historical drought and wetting shape post‐event soil carbon fluxes remains poorly understood. Using a seven‐year precipitation manipulation experiment (−70% to +50%) followed by a two‐year recovery period in a semi‐arid grassland, we quantified legacy effects on soil respiration (Rs) and its autotrophic (Ra) and heterotrophic (Rh) components. Historical moderate wetting (+30%) generated the strongest positive legacy, increasing Rs, Rh, and Ra by 21.9%, 24.4%, and 26.9%, respectively, during the first recovery year. In contrast, historical drought treatments (−70% to −30%) produced biphasic legacies, characterized by early‐season suppression followed by later‐season positive responses, potentially associated with decomposition of drought‐accumulated substrates and vegetation recovery. Ra generally showed stronger recovery responses than Rh, indicating contrasting sensitivities of plant‐ and microbially ‐ derived respiration to moisture and carbon availability. The dominant controls of respiration also shifted over time: first‐year legacies were associated mainly with microbial carbon substrates and extracellular enzyme activities, whereas second‐year responses were increasingly linked to plant allocation strategy and microbial community composition. Despite these contrasting trajectories, Rs, Ra, and Rh largely converged to control levels within two years. Our results demonstrate that precipitation legacies in semi‐arid grasslands are asymmetric and temporally dynamic, with important implications for predicting carbon cycling under increasing hydrological variability.

Histone H3K4 monomethyltransferase SETD7 promoted osteogenic differentiation of bone marrow mesenchymal stem cells exposed to Hydroquinone via autophagy - Yilin Shen; Yibo Niu; Tao Xu; Zhilong Luo; Donghao Song; Chiheng Luo; Yan Liu; Qilin Cui; Dongxiao Chen; Xinyu Zhao; Hao Luo; Yuting Gao (Toxicology Letters, 2026)

Mechanisms, influencing factors, removal effectiveness and electrochemically enhanced technologies of tidal flow constructed wetlands - Chunyao Zhao; Yuqing Yang; Xiaoheng Wang; Peiyang Zhang; Bohan Fang; Yuting Zhong; Ke Zhao; Zhen Hu; Erping Cui; Jianan Li (Journal of Environmental Chemical Engineering, 2026)

Range-wide phenotypic variation in fruit and seed traits of Cyclocarya Paliurus across environmental gradients in China - Wanxia Yang; Yuting Cen; Yichen Cui; Xiaoqiang Lu; Shengzuo Fang (Plant Ecology, 2026)

First report of Stemphylium lycopersici causing postharvest fruit rot of pepino in China - Xinyue Wang; Zihuan Liu; Yuting Qi; Dianming Hu; Haiyan Song; Chaoyu Cui (Journal of Plant Pathology, 2026)

Development and application of integrated adsorption–fluidized-bed desorption–RTO process for high-flowrate rubber vulcanization exhaust - Shanshan Guo; Boxian Chen; Yufei Cai; Cui Li; Ling Ma; Zhentao Wang; Yuting Huang; Weibing Wu; Ke Jin; Xingyu Jiang; Weirong Zhao (Chemical Engineering Journal, 2026)

Refined shearing of cellulose nanocrystals for controllable interference color patterns - Yuting Wu; Yande Cui; Yanduo Zhai; Chunyu Chang (Chemical Engineering Journal, 2026)

In situ spermidine-integrated dynamic hyaluronic acid-based hydrogels platforms for anti-inflammation and anti-fibrosis in subconjunctival injuries - Haohao Cui; Yuting Deng; Boyuan An; Qingyun Ning; Xue Sun; Mengke Wang; Xing Wang; Zhihua Guo; Zhanrong Li; Shaokui Cao; Jingguo Li (Carbohydrate Polymers, 2026)

RAD51 m6A and PARylation modification orchestrate benzene-induced haematological toxicity - Lin Chen; Fengzhen Cui; Han Li; YuTao Zeng; Zhongming Wu; Weitian Chen; Qiaosheng Wen; Chunnian You; Yunqiang Xu; Lei Sun; Mingwei Sun; Qian Sun; et al. (Journal of Hazardous Materials, 2026)

Intrinsic ultralow Dk/Df polyimides with hydrophobicity and high adhesion based on a molecular threading and interlocking mechanism - Xi He; Yuting Duan; Kangle Xue; Xiaorong Guo; Chao Cui; Yudong Huang (Chemical Engineering Journal, 2026)

Pasteurized Akkermansia muciniphila ameliorates insulin resistance by reducing placental inflammation in GDM mouse model - Yi Wang; Yuting Zhu; Yan Cui; Jiali Fang; Hong Zhong; Yujie Shi; Lan Liu; Xianwei Cui (Reproductive Biology, 2025)

Regulating electronegativity difference and piezoelectric strain of the Mo-S-Mo structure via introducing S vacancies for boosting piezo-photoelectric activity - Yanjiao Li; Yuting Ning; Xinping Fu; Yu Jiang; Lianfeng Wang; Jun Cui (Journal of Environmental Chemical Engineering, 2025)

Coliforms and Salmonella cross-contamination in retail frozen chicken and its contact ice, with global surveillance of chicken-derived Salmonella and S. Bareilly - Qiuping Yang; Yuting Huang; Yanan Wang; Yiyou Liang; Shousheng Feng; Chang Liu; Yinuo Yang; Qing Liu; Kaige Yang; Wei Zhou; Shenghui Cui; Baowei Yang (Food Research International, 2025)

The relationship between outdoor thermal environment, individual thermal exposure, and chest skin temperature: A field study in real-life conditions - Wenli Jian; Ruyi Liang; Yuxin Yao; Yuyang Zhao; Yichen Liu; Anqi Guan; Jiarui Hu; Yuting Wang; Bin Wang; Jing Wang; Yuchen Hou; Yingxin Zhu; et al. (Energy and Buildings, 2025)

Synergistic valorization of red mud and spent coffee grounds via one-step hydrothermal carbonization for high-efficiency Pb(II) and Cd(II) removal from wastewater - Yuting Cui; Yue Zhou; Mingqian Cheng; Wei Fang; Yaoling Wang; Chao Chen; Tingting Liu; Bin Li; Zewei Liu (Desalination, 2025)

Meiotic cytokinesis defects in cultured Arabidopsis flowers induce diploid microspores - Huiqi Fu; Yuting Chen; Xueying Cui; Huishan He; Jingru Wang; Chong Wang; Ziming Ren; Bing Liu (Plant Reproduction, 2025)

PufH: A promising biocatalyst for the recycling and bioremediation of polyurethane foam waste - Yuting Jiang; Mingliang Zhang; Jie Zhou; Zhongli Cui; Qing Hong; Weiliang Dong; Xin Yan (Journal of Hazardous Materials, 2025)

Iron-doped and nitrogen-deficient tubular carbon nitride enables synergistic photocatalysis-self-Fenton degradation of tetracycline - Fan Fan; Jiajie Yu; Junjie Jiang; Hao Xiu; Yuting Wang; Yongpeng Cui; Yajun Wang (Journal of Environmental Chemical Engineering, 2025)

Non-targeted identification and risk classification for chemical migrants in 41 disposable biodegradable tableware - Yuting Chen; Xiaomeng Gao; Guowei Ma; Liqian Wang; Peixue Guo; Yiling Cui; Jingwei Zhang; Di Feng (Food Bioscience, 2025)

Exploring the links between wetland design parameters, hydraulic behaviors, and treatment performance using an improved analysis framework - Bochao Zhang; Junzhe Luo; Yuting Zhang; Jiaer Wang; Chi Tang; Yufeng Luo; Yuanlai Cui (Journal of Hydrology, 2025)

Enhanced HCl resistance of Na-Ce/Al2O3 hydrolysis catalyst to boost blast furnace gas purification - Yuting Lin; Yuran Li; Qiang Cao; Jianshan Wang; Yanbin Cui; Tingyu Zhu (Journal of Cleaner Production, 2025)

Mechanisms of reactive intermediates formation in saline-alkali agricultural waters - Xinyi Wang; Jiyang Liu; Songyang Li; Yaqin Miao; Yuting Shen; Hu Cui; Shengnan Hou; Hui Zhu (Water Research, 2025)

Floating-leaved and submerged macrophytes suppress filamentous cyanobacteria blooms and 2-MIB episodes in eutrophic shallow lakes - Zhijie Cui; Changtao Yang; Limin Ma; Xiaoyan Gu; Xiaobing Shen; Bin Wan; Yuwei Tao; Yuting Sang; Qinghui Huang (Journal of Hazardous Materials, 2025)

Chemical migration, digestive behaviors and effect on gut microbiota of PLA and PBAT oligomers - Guowei Ma; Xiaomeng Gao; Yuting Chen; Hanfei Li; Yiling Cui; Peixue Guo; Tingting Zhao; Feng Di (Journal of Hazardous Materials, 2025)

Mercury accumulation in urban forest leaves: Dynamics, driving factors, and potential economic value - Yuliang Xiao; Hongjie Zhang; Jing Zong; Xinyu Bai; Kaili Yang; Xuemei Li; Xin Huang; Yufei Hu; Yuting Bao; Abdur Razzaq; Dan Cui; Zhaojun Wang; et al. (Journal of Hazardous Materials, 2025)

Endocrine-disrupting effects of 24 colorants used in food contact materials: In vitro and in silico studies - Guowei Ma; Yiling Cui; Qian Li; Yuting Chen; Peixue Guo; Di Feng; Tingting Zhao (Food and Chemical Toxicology, 2025)

Effects of leptin on fatty acid metabolism in the liver and reproductive function of tongue sole (Cynoglossus semilaevis) in vivo - Xin Cai; Yuting Li; Zhaojun Meng; Aijun Cui; Yan Jiang; Yongjiang Xu (Aquaculture, 2025)

Experimental investigation on the formation and failure of landslide dams considering the landslide mobility and river flow - Hongwei Luo; Gordon G.D. Zhou; Xueqiang Lu; Kahlil F.E. Cui; Yuting Zhao; Yunxu Xie; Wei Zhong; Jiawen Zhou; Alessandro Pasuto (Engineering Geology, 2025)

Vocalization-induced middle ear muscle reflex and auditory fovea do not contribute to the unimpaired auditory sensitivity after intense noise exposure in the CF-FM bat, Hipposideros pratti - Zhongdan Cui; Jianwen Zou; Yuting Zhou; Yuntu Cao; Haonan Song; Haoyue Xu; Jing Wu; Baoling Jin; Lijian Yang; Ya Jia; Qicai Chen; Ziying Fu (Journal of Comparative Physiology A, 2025)

Spatial variations and vertical migration potentials of petroleum hydrocarbons with varying chain lengths in soils of different depths: Roles of solid and dissolved organic matters and soil texture - Aiai Shu; Zhenglun Yang; Qianqian Cui; Zhaoyang Liu; Shun Liu; Mancheng Zhang; Heyang Sun; Jiaqi Shang; Huirui Tian; Yuting Xiao; Wenfeng Tan (Science of The Total Environment, 2024)

A MOF-on-MOF heterostructure ratiometric/colorimetric dual-mode fluorescence sensor based on support vector machine for detecting tetracyclines in animal-derived foods - Zhehang Tian; Xieyang Zhang; Yuting Zhang; Zimeng Wu; Guanqun Luan; Luqian Bao; Yixin Ji; Mengyao Cui; Chunhua Li (Food Chemistry, 2024)

Biological pretreatment and co-digestion strategies enhance the methane yield of waste wool - Xiaotian Chen; Yuting Xie; Changchang Zang; Weiwei Wang; Jinxiang Tian; Boting Wen; Zongjun Cui; Xufeng Yuan (Chemical Engineering Journal, 2024)

Systemic immune inflammation index with all-cause and cause-specific mortality: a meta-analysis - Wei Li; Xiaoning Wang; Houze Diao; Yuting Yang; Liyi Ding; Wenru Huan; Yaozhi Chen; Weiwei Cui (Inflammation Research, 2024)

Advanced review on type II collagen and peptide: preparation, functional activities and food industry application - Pengbo Cui; Tianlun Shao; Weilin Liu; Mengyu Li; Mingxiao Yu; Weixue Zhao; Yanzhuo Song; Yuting Ding; Jianhua Liu (Critical Reviews in Food Science and Nutrition, 2024)

Efficient reclamation of phosphorus from wetland biomass waste via liquid-recirculated hydrothermal carbonization and precipitation - Junxia Wang; Yuting Wang; Fan Yu; Jiangtao Wang; Xutong Wang; Jipeng Luo; Chao He; Xiaoqiang Cui; Beibei Yan; Guanyi Chen (Water Research, 2024)

Effective adsorption performance and mechanism of methylene blue from dye wastewater by humic acid sucrose-modified red mud - Wei Fang; Yue Zhou; Mingqian Cheng; Jinzhong Yang; Qifei Huang; Zechun Huang; Yuting Cui; Liping Zhang; Yushu Wang; Qihong Cen; Zewei Liu; Bin Li (Process Safety and Environmental Protection, 2024)

Evaluation of potential evapotranspiration models over fluxdata network cropland sites - Ziling He; Shouzheng Jiang; Yu Feng; Lu Zhao; Jun Li; Yuting Zhang; Ningbo Cui (Journal of Hydrology, 2024)

Porous hollow microspheres based on industrial solid waste enhance biomethane recovery from corn straw - Xiaotian Chen; Changchang Zang; Yuting Xie; Ke Wang; Yang Li; Ruifang Lv; Boting Wen; Zongjun Cui; Xufeng Yuan (Bioresource Technology, 2024)

Greenhouse gases emissions and microbial assembly mechanism in constructed wetlands for treating saline-alkali and fluoride-laden drainage water - Yaqin Miao; Yuting Shen; Shengnan Hou; Hu Cui; Weihong Zhu; Hui Zhu (Chemical Engineering Journal, 2024)

Global, regional, and national burden of cancers attributable to particulate matter pollution from 1990 to 2019 and projection to 2050: Worsening or improving? - Junyan Chen; Yuanyao Cui; Ye Deng; Yuting Xiang; Jiamei Chen; Yuting Wang; Tianyun Wang; Miao He (Journal of Hazardous Materials, 2024)

Transcriptome analysis reveals polyploidy-related differential gene expression among diploid, triploid, and tetraploid Pacific oysters (Crassostrea gigas) based on growth-related phenotypes - Luyao Dong; Zan Li; Weijun Wang; Yuting Meng; Enshuo Zhang; Xuebo Cui; Xiaohui Xu; Yanwei Feng; Guohua Sun; Zhongping Wang; Jianmin Yang (Aquaculture, 2024)

Greenhouse gases emissions and carbon budget estimation in horizontal subsurface flow constructed wetlands with different plant species - Sile Hu; Weidong Feng; Yuting Shen; Xiaoling Jin; Yaqin Miao; Shengnan Hou; Hu Cui; Hui Zhu (Science of The Total Environment, 2024)

Degradable ZIF-8/silica carriers with accropode-like structure for enhanced foliar affinity and responsive pesticide delivery - Menghui Wan; Yuting Zhang; Tao Hong; Junyan Cui; Yanbao Zhao; Zhihua Wang (Chemical Engineering Journal, 2024)

Effects of Different Forms of Sulfur on Plant Growth and Soil Properties in Cadmium-Contaminated Soils - Honglei Jia; Cui Chen; Qing Wang; Yuting Wei; Junkang Guo; Chunping Zhang; Guangfang Wu; Ting Wei; Xinhao Ren; Chao Zhang; Jisheng Li (Journal of Soil Science and Plant Nutrition, 2024)

Divergent growth and responses of conifer and broad-leaved trees to warming-drying climate in a semi-arid region, northern China - Ying Zhao; Junxia Li; Yuting Jin; Tsun Fung Au; Di Cui; Zhenju Chen (European Journal of Forest Research, 2024)

Life cycle assessment for evaluation of novel solvents and technologies: A case study of flavonoids extraction from Ginkgo biloba leaves - Xuan Wang; Yuting Wei; Zhenyan Fan; Yueyuan Chen; Zhifang Cui (Science of The Total Environment, 2024)

Roles of red mud in remediation of contaminated soil in mining areas: Mechanisms, advances and perspectives - Yue Zhou; YuTing Cui; Jinzhong Yang; Ling Chen; Jiamin Qi; Liping Zhang; Jin Zhang; Qifei Huang; Tao Zhou; Youcai Zhao; Zewei Liu; Bin Li (Journal of Environmental Management, 2024)

A multifunctional interface optimization strategy for efficient Quasi-2D blue perovskite Light-Emitting diodes - Yuliang Ye; Zhou Cui; Zunxian Yang; Zhiwei Zeng; Zongyi Meng; Hongyi Hong; Songwei Ye; Zhiming Cheng; Qianting Lan; Jiaxiang Wang; Ye Chen; Hui Zhang; et al. (Chemical Engineering Journal, 2024)

Quantifying the spatial inhomogeneity of ice concentration in mixed-phase stratiform cloud using airborne observation - Yuting Deng; Jing Yang; Yan Yin; Shiqi Cui; Bo Zhang; Xinghua Bao; Baojun Chen; Junxia Li; Wei Gao; Xiaoqin Jing (Atmospheric Research, 2024)

The concentration of CH4, N2O and CO2 in the Pearl River estuary increased significantly due to the sediment particle resuspension and the interaction of hypoxia - Shuangyuan Liu; Quanzhou Gao; Jiaxue Wu; Yuting Xie; Qianqian Yang; Ruowen Wang; Yongsheng Cui (Science of The Total Environment, 2024)

Spatial variations in water use efficiency across global terrestrial ecosystems - Shuyan Cui; Yushan Xiao; Yuting Yang; Zhongmin Hu; Guo Zheng (CATENA, 2024)

Phased genome assemblies reveal haplotype‐specific genetic load in the critically endangered Chinese Bahaba (Teleostei, Sciaenidae) - Rongfeng Cui; Jinxian Wu; Kuoqiu Yan; Sujun Luo; Yuting Hu; Wei Feng; Bingqian Lu; Junjie Wang (Molecular Ecology, 2024)
While haplotype‐specific genetic load shapes the evolutionary trajectory of natural and captive populations, mixed‐haplotype assembly and genotyping hindered its characterization in diploids. Herein, we produced two phased genome assemblies of the critically endangered fish Chinese Bahaba ( Bahaba taipingensis , Sciaenidae, Teleostei) and resequenced 20 whole genomes to quantify population genetic load at a haplotype level. We identified frame‐shifting variants as the most deleterious type, followed by mutations in the 5′‐UTR, 3′‐UTR and missense mutations at conserved amino acids. Phased haplotypes revealed gene deletions and high‐impact deleterious variants. We estimated ~1.12% of genes missing or interrupted per haplotype, with a significant overlap of disrupted genes (30.35%) between haplotype sets. Relative proportions of deleterious variant categories differed significantly between haplotypes. Simulations suggested that purifying selection struggled to purge slightly deleterious genetic load in captive breeding compared to genotyping interventions, and that higher inter‐haplotypic variance of genetic load predicted more efficient purging by artificial selection. Combining the knowledge of haplotype‐resolved genetic load with predictive modelling will be immensely useful for understanding the evolution of deleterious variants and guiding conservation planning.

Deciphering microbiomes dozens of meters under our feet and their edaphoclimatic and spatial drivers - Haoran He; Jingxiong Zhou; Yunqiang Wang; Shuo Jiao; Xun Qian; Yurong Liu; Ji Liu; Ji Chen; Manuel Delgado‐Baquerizo; Albert C. Brangarí; Li Chen; Yongxing Cui; et al. (Global Change Biology, 2024)
Microbes inhabiting deep soil layers are known to be different from their counterpart in topsoil yet remain under investigation in terms of their structure, function, and how their diversity is shaped. The microbiome of deep soils (>1 m) is expected to be relatively stable and highly independent from climatic conditions. Much less is known, however, on how these microbial communities vary along climate gradients. Here, we used amplicon sequencing to investigate bacteria, archaea, and fungi along fifteen 18‐m depth profiles at 20–50‐cm intervals across contrasting aridity conditions in semi‐arid forest ecosystems of China's Loess Plateau. Our results showed that bacterial and fungal α diversity and bacterial and archaeal community similarity declined dramatically in topsoil and remained relatively stable in deep soil. Nevertheless, deep soil microbiome still showed the functional potential of N cycling, plant‐derived organic matter degradation, resource exchange, and water coordination. The deep soil microbiome had closer taxa–taxa and bacteria–fungi associations and more influence of dispersal limitation than topsoil microbiome. Geographic distance was more influential in deep soil bacteria and archaea than in topsoil. We further showed that aridity was negatively correlated with deep‐soil archaeal and fungal richness, archaeal community similarity, relative abundance of plant saprotroph, and bacteria–fungi associations, but increased the relative abundance of aerobic ammonia oxidation, manganese oxidation, and arbuscular mycorrhizal in the deep soils. Root depth, complexity, soil volumetric moisture, and clay play bridging roles in the indirect effects of aridity on microbes in deep soils. Our work indicates that, even microbial communities and nutrient cycling in deep soil are susceptible to changes in water availability, with consequences for understanding the sustainability of dryland ecosystems and the whole‐soil in response to aridification. Moreover, we propose that neglecting soil depth may underestimate the role of soil moisture in dryland ecosystems under future climate scenarios.

Effects of Recombinant Leptin Proteins on the Expression of Key Genes in the HPG Axis and Liver of Tongue Sole In Vitro - Xin Cai; Yaxing Zhang; Bin Wang; Aijun Cui; Yan Jiang; Zhaojun Meng; Yuting Li; Yongjiang Xu (Fishes, 2023)
Leptin (Lep) plays a crucial role in controlling food intake and maintaining energy balance in mammals. While several studies have shown the presence of multiple leptin genes in teleosts, limited information is currently available on how sex steroid hormones regulate the expression of these genes in fish. In this study, we used two previously expressed and purified leptin proteins to incubate four tissues in vitro (hypothalamic-pituitary-gonadal axis and liver) and used the RT-qPCR method to detect the expression of genes related to growth and reproduction in tongue sole (Cynoglossus semilaevis). The results showed that both recombinant LepA and LepB proteins of tongue sole almost entirely suppressed the expression of genes related to growth and reproduction in the hypothalamic-pituitary-gonadal axis and liver, while LepB may have had a positive role on steroid synthesis in gonads. Further, a high concentration of LepA facilitated the expression of IGF-Ι in liver. At the same time, we utilized human leptin to incubate four tissues in vitro; although most of them had trends similar to those stimulated with tongue sole leptins, there were still some differences, indicating differences among leptin homologs between humans and fishes. To our knowledge, this is the first study to explore the function of tongue sole LepA and LepB within the hypothalamic-pituitary-gonadal axis and liver in vitro. Our results provide a valuable resource and foundation for future studies.

Mitigating ammonia volatilization in rice cultivation: The impact of partial organic fertilizer substitution - Bin Liao; Ping Liao; Ronggui Hu; Tianchi Cai; Yuting Zhang; Qian Yu; Bochao Zhang; Yonghong Shu; Jiaer Wang; Yufeng Luo; Yuanlai Cui (Chemosphere, 2023)

MiR-7-5p targeted Rb regulating cell cycle is involved in hydroquinone-induced malignant progression in human lymphoblastoid TK6 cells - Lu Zhai; Yuting Gao; Zheming Cui; Lin Chen; Lingxue Yu; Pu Guo; Delong Zhu; Huanwen Tang; Xin Liu; Hao Luo (Food and Chemical Toxicology, 2023)

Halophilic microalga-based circular economy producing functional food by reclaiming high-salinity seafood processing sewage - Yuting Chen; Chanyuan Song; Xinyu Cui; Jiakun Han; Kalyanee Paithoonrangsarid; Qinhua Gan; Yandu Lu (Biomass and Bioenergy, 2023)

Low-carbon economic dispatch of integrated energy systems that incorporate CCPP-P2G and PDR considering dynamic carbon trading price - Yang Cui; Yang Xu; Tao Huang; Yijian Wang; Dingran Cheng; Yuting Zhao (Journal of Cleaner Production, 2023)

A combination of organic fertilizers partially substitution with alternate wet and dry irrigation could further reduce greenhouse gases emission in rice field - Bin Liao; Tianchi Cai; Xian Wu; Yue Luo; Ping Liao; Bochao Zhang; Yuting Zhang; Guangfei Wei; Ronggui Hu; Yufeng Luo; Yuanlai Cui (Journal of Environmental Management, 2023)

Phase-modulated built-in electric field to boost photogenerated electron migration for efficient dehalogenation - Meng Ren; Pengjie Zhao; Xinping Fu; Meng Liu; Yuting Ning; Yinjie Zhang; Chunyan Wang; Aijun Lin; Jun Cui (Chemical Engineering Journal, 2023)

Construction of submicro rhombic RDX lamellae and the critical size effect on desensitivity originated from slipping energy dissipation - Yuxin Cui; Xun Liu; Liangyou Zhao; Yuanyuan Deng; Yuting Li; Xiaohui Duan; Bo Wu; Chonghua Pei (Chemical Engineering Journal, 2023)

Can the development of renewable energy in China compensate for the damage caused by environmental pollution to residents’ health? - Chenggang Li; Xiangbo Fan; Yuting Wang; Zuogong Wang; Yunxiao Dang; Yuanzheng Cui (Environmental Science and Pollution Research, 2023)

Effect of low voltage electrostatic field combined with partial freezing on the quality and microbial community of large yellow croaker - Jianyou Zhang; Lifeng Fei; Pengbo Cui; Noman Walayat; Shengqiang Ji; Yiling Chen; Fei Lyu; Yuting Ding (Food Research International, 2023)

Cloning, characterization and expression analysis of a brassinosteroids biosynthetic gene VvDET2 in Cabernet Sauvignon (Vitis vinifera L.) - Jingwen Cui; Guihua Zeng; Feifei Gao; Yue Jiang; Yuting Wang; Dandan Li; Xuefei Wang; Zhumei Xi (Plant Cell, Tissue and Organ Culture (PCTOC), 2023)

Production of potassium-enriched biochar from Canna indica: Transformation and release of potassium - Guanyi Chen; Yuting Wang; Jiangtao Wang; Junxia Wang; Fan Yu; Qingxu Ma; Zhanjun Cheng; Beibei Yan; Yuchao Song; Xiaoqiang Cui (Waste Management, 2023)

Ruthenium nanoparticles loaded on N/P co-doped carbon sphere derived from sphere cross-linked hydrogel for highly improved hydrogen evolution reaction - Hai Lan; Yuting Yang; Yi Wu; Miao Liu; Fei Li; Feng Wang; Xudong Cui; Taotao Gao (Fuel, 2023)

Effects of combined treatment of electrolytic water and chitosan on the quality and proteome of large yellow croaker (Pseudosciaena crocea) during refrigerated storage - Jianyou Zhang; Lei Sun; Pengbo Cui; Ligen Zou; Yutong Chen; Jianqin Liang; Shengqiang Ji; Noman Walayat; Fei Lyu; Yuting Ding (Food Chemistry, 2023)

Root exudation processes induce the utilization of microbial-derived components by rhizoplane microbiota under conservation agriculture - Yüze Li; Mei Long; Yuting Hou; Wei Li; Xiaoliang Qin; Baogang Zhang; Tao Wen; Yongxing Cui; Ziting Wang; Yuncheng Liao (Soil Biology and Biochemistry, 2023)

Targeted therapy for autoimmune diseases based on multifunctional frame nucleic acid system: Blocking TNF-α-NF-κB signaling and mediating macrophage polarization - Mei Zhang; Yuting Wen; Zhangheng Huang; Xin Qin; Mi Zhou; Dexuan Xiao; Weitong Cui; Zhiqiang Liu; Yunfeng Lin (Chemical Engineering Journal, 2023)

Removal of fluoride from aqueous solutions through Fe(III) modified water treatment residues - Kai Ning; Shaocheng Zheng; Yuting He; Yun Hu; Shiyou Hao; Qingliang Cui; Hansong Chen (Journal of Cleaner Production, 2023)

High-efficiency control of pesticide and heavy metal combined pollution in paddy soil using biochar/g-C3N4 photoresponsive soil remediation agent - Hantong Qie; Meng Ren; Chang You; Xuedan Cui; Xiao Tan; Yuting Ning; Meng Liu; Daibing Hou; Aijun Lin; Jun Cui (Chemical Engineering Journal, 2023)

BCI system with lower-limb robot improves rehabilitation in spinal cord injury patients through short-term training: a pilot study - Zhengzhe Cui; Yongqiang Li; Sisi Huang; Xixi Wu; Xiangxiang Fu; Fei Liu; Xiaojiao Wan; Xue Wang; Yuting Zhang; Huaide Qiu; Fang Chen; Peijin Yang; et al. (Cognitive Neurodynamics, 2022)

A neuropsin-based optogenetic tool for precise control of Gq signaling - Ruicheng Dai; Tao Yu; Danwei Weng; Heng Li; Yuting Cui; Zhaofa Wu; Qingchun Guo; Haiyue Zou; Wenting Wu; Xinwei Gao; Zhongyang Qi; Yuqi Ren; et al. (Science China Life Sciences, 2022)

Correction to: GLP-1 Receptor Agonist Inhibited the Activation of RIPK1 for Alleviation the Neuronal Death and Neuroinfammation in APP/PS1 Mice - Xiaodong Kong; Yuting Yang; Huijie Li; Weiyun Cui; Xiaohui Wu; Min Gong; Ying Li (International Journal of Peptide Research and Therapeutics, 2022)

GLP-1 Receptor Agonist Inhibited the Activation of RIPK1 for Alleviation the Neuronal Death and Neuroinflammation in APP/PS1 Mice - Xiaodong Kong; Yuting Yang; Huijie Li; Weiyun Cui; Xiaohui Wu; Min Gong; Ying Li (International Journal of Peptide Research and Therapeutics, 2021)

Equivalent effect of extracellular proteins and polysaccharides on biofilm formation by clinical isolates of Staphylococcus lugdunensis - Weidong Qian; Wenjing Wang; Jianing Zhang; Miao Liu; Yuting Fu; Mingming Li; Jing Jin; Wei Cui; Chengbin Wang (Biofouling, 2021)

Microalgal-bacterial granular sludge process outperformed aerobic granular sludge process in municipal wastewater treatment with less carbon dioxide emissions - Dabin Guo; Xuechun Zhang; Yuting Shi; Baihui Cui; Jie Fan; Bin Ji; Julin Yuan (Environmental Science and Pollution Research, 2021)

Transcriptomic Analysis of Pacific Oyster (Crassostrea gigas) Zygotes Under Hypotonic Triploid Induction - Yangchun Li; Zhaoping Wang; Yuting Cui; Peizhen Ma; Xuekai Zhang; Chao Fan (Journal of Ocean University of China, 2021)

Recent progress in the use of mitochondrial membrane permeability transition pore in mitochondrial dysfunction-related disease therapies - Yuting Cui; Mingyue Pan; Jing Ma; Xinhua Song; Weiling Cao; Peng Zhang (Molecular and Cellular Biochemistry, 2021)

Dihydroartemisinin ameliorates LPS-induced neuroinflammation by inhibiting the PI3K/AKT pathway - Yuting Gao; Miaomiao Cui; Sijin Zhong; Chenyao Feng; Alexander Kenechukwu Nwobodo; Bin Chen; Yuanjian Song; Yulan Wang (Metabolic Brain Disease, 2020)

Research on the influence of land use change to habitat of cranes in Shengjin Lake wetland - Lei Fang; Bin Dong; Cheng Wang; Fei Yang; Yanglin Cui; Wenrui Xu; Liang Peng; Yuting Wang; Haoran Li (Environmental Science and Pollution Research, 2020)

ALFF Value in Right Parahippocampal Gyrus Acts as a Potential Marker Monitoring Amyotrophic Lateral Sclerosis Progression: a Neuropsychological, Voxel-Based Morphometry, and Resting-State Functional MRI Study - Wenjia Zhu; Xiaoling Fu; Fang Cui; Fei Yang; Yuting Ren; Xiaoyun Zhang; Xiaolan Zhang; Zhaohui Chen; Li Ling; Xusheng Huang (Journal of Molecular Neuroscience, 2015)